Realitas Phone Snubbing pada Pergaulan Remaja - Dina Alamianti; Rannie Dyah K Rachaju (COMMUNICATION MAJOR, 2021)
Abstract Excessive use of gadgets can lead to phone snubbing behaviour, in this case, teenagers become indifferent to their environment and more focus on playing with their gadgets. The reality of phone snubbing (phubbing) can cause communication barriers such as distortion of messages and cause interpersonal relationships to become disrupted. This research aimed to (1) find out the role of communication actors in phone snubbing reality specifically in adolescent relationships’ framework, (2) verbal and nonverbal messages in the reality of phone snubbing, and (3) the meaning of phone snubbing for adolescents. The method used in this research is qualitative, with data collection techniques through in-depth interviews, observations, and documentation. Informants of this research are Bandung’s high school students who actively use their gadget. This research concluded that there was a title role in the interaction process of phone snubbing reality, individuals became the committers of communication known as phubber, that is an affected person phubbing, and phubbed as phubbing actors. Verbal messages occur in concurrence with nonverbal messages in the interaction of high school teenager’s communication in the form of school chats, gossip, and funny stories accompanied by nonverbal indicated from the closeness of their friendships, there is a ritual touching base message, such as patting the friends’ shoulders and the friendship affectionate display. Phubbing behaviour is felt more obvious when they engaged in family’s interaction. Phubbing is defined as unlikable behaviour and can interfere with friendships.Keywords: Gadget; Interpersonal Communication; Phone Snubbing; TeenagerAbstrak Penggunaan gawai yang berlebihan pada remaja dapat menimbulkan perilaku phone snubbing, yaitu kondisi dimana remaja menjadi acuh terhadap lingkungannya dan lebih berfokus bermain dengan gawainya. Realitas phone snubbing (phubbing) dapat menimbulkan hambatan komunikasi seperti distorsi pesan dan mngakibatkan hubungan interpersonal menjadi terganggu. Penelitian ini bertujuan untuk mengetahui peran pelaku komunikasi dalam realitas phone snubbing pada pergaulan remaja, pesan verbal dan nonverbal dalam realitas phone snubbing, serta makna phone snubbing bagi remaja. Metode yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Informan penelitian ini adalah siswa Sekolah Menengah Atas (SMA) yang aktif menggunakan gawainya di Kota Bandung. Hasil penelitian menunjukkan bahwa terjadi pengambilan peran pada proses interaksi dalam realitas phone snubbing dimana individu menjadi pelaku phubber yaitu seorang terdampak phubbing dan phubbed sebagai pelaku phubbing. Pesan verbal terjadi bersamaan dengan pesan nonverbal pada interaksi komunikasi remaja SMA berupa obrolan sekolah, gosip, dan cerita lucu. Pesan non verbal ditunjukkan dengan hubungan pertemanan yang akrab misalnya penyampaian pesan sentuhan ritual yaitu menepuk pundak teman serta adanya affect display. Perilaku phubbing lebih dirasakan dalam konteks interaksi komunikasi pada keluarga. Phubbing dimaknai sebagai perilaku yang tidak disukai dan dapat mengganggu hubungan pertemanan.Kata Kunci: Gawai; Komunikasi Interpersonal; Phone Snubbing; Remaja